Transnational Relations and Activism in International Relations: Debates and Consensus in Literature - Soetjipto, Ani Widyani; Yuliestiana, Arivia Tri Dara (Global: Jurnal Politik Internasional, 2020)
This article explores the concepts of transnational relations and activism in the study of International Relations, specifically the role of civil society in transnational advocacy. It becomes fascinating to discuss the role of civil society when state actors are no longer the most prominent actors in International Relations studies in the midst of globalization. Some articles related to transnational relations were written by the scholars of International Relations such as Thomas Risse-Kappen (1995). Even so, one of the most sophisticated concepts of transnational activism was introduced by Margaret Keck and Kathryn Sikkink (1998), in the “Activists Beyond Borders: Advocacy Networks in International Politics.” In order to fully understand transnational activism in the study of International Relations, a divergent perspective can be applied. In this article, the authors aim to examine the recent debates and its counternarratives in International Relations through critical and contructivism lenses. Firstly, this article would describe the concepts of transnationalism and transnational activism in the study of International Relations (state of the art). Secondly, it would be a discussion in the literature on transnationalism and transnational activism which cover themes about norm diffusion, the ‘boomerang pattern’, political opportunity structures and accountability and effectiveness. The last part is conclusion that can be drawn from this consensus and debates in the concept of transnational activism.